Arteriovenous access placement and renal function decline. Issue 2 (30th October 2019) - Hahn Lundström, Ulrika; Hedin, Ulf; Gasparini, Alessandro; Caskey, Fergus J; Carrero, Juan-Jesus; Evans, Marie
Abstract: Background: There is controversial evidence on whether arteriovenous access (AVA) placement may protect renal function and hence should be considered in the timing of access placement. This study aimed to investigate the association between AVA placement and estimated glomerular filtration rate (eGFR) decline as compared with the placement of a peritoneal dialysis catheter (PDC) at a similar time point. Methods: We studied a cohort of 744 pre-dialysis patients in Stockholm, Sweden, who underwent surgery for AVA or PDC between 2006 and 2012. Data on comorbidity, medication and laboratory measures were collected 100 days before and after surgery. Patients were followed until dialysis start, death or 100 days, whichever came first. The primary outcome was difference in eGFR decline after AVA surgery compared with PDC. Decline in eGFR was estimated through linear mixed models with random intercept and slope, before and after surgery. Results: There were 435 AVA and 309 PDC patients. The AVA patients had higher eGFR (8.1 mL/min/1.73 m 2 versus 7.0 mL/min/1.73 m 2 ) and less rapid eGFR decline before surgery (−5.6 mL/min/1.73 m 2 /year compared with −6.7 mL/min/1.73 m 2 /year for PDC). We found no difference in eGFR decline after surgery in AVA patients compared with PDC patients [AVA progressed 0.26 (95% confidence interval −0.88 to 0.35) mL/min/1.73 m 2 /year faster after surgery compared with PDC]. Conclusions: There was no significant difference in eGFR decline after placement of an AVA compared with a PDC. Both forms of access were associated with reduced eGFR decline in our population. The need for dialysis remains the main determinant for timing of access surgery.